Bactericidal wet-spun cellulose acetate/polycaprolactone fibers: impact of cinnamon, clove and cajeput essential oils loaded onto the surface - Felgueiras, Helena Prado (2021)
[Excerpt] Essential oils (EOs), which are complex biomolecules composed of volatile compounds, have emerged as a new strategy to deal with bacterial infections and as a valid alternative to synthetic drugs in the treatment of chronic wounds (CW) by promoting the regeneration of damaged tissues.